If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 9 = -9t + -13 Reorder the terms: 9 + 4t = -9t + -13 Reorder the terms: 9 + 4t = -13 + -9t Solving 9 + 4t = -13 + -9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '9t' to each side of the equation. 9 + 4t + 9t = -13 + -9t + 9t Combine like terms: 4t + 9t = 13t 9 + 13t = -13 + -9t + 9t Combine like terms: -9t + 9t = 0 9 + 13t = -13 + 0 9 + 13t = -13 Add '-9' to each side of the equation. 9 + -9 + 13t = -13 + -9 Combine like terms: 9 + -9 = 0 0 + 13t = -13 + -9 13t = -13 + -9 Combine like terms: -13 + -9 = -22 13t = -22 Divide each side by '13'. t = -1.692307692 Simplifying t = -1.692307692
| -3(1+w)+4w=8 | | -6x+36=28 | | 8-(2x-6)=22 | | 4+8y+9n-2y-2n-17= | | -p^2+8p+4= | | 4z+3(z+7)=-14 | | 2(x-2y-7z)= | | -4p^3+32p^2+16p= | | 2(9x-8)= | | 2(a+5)-a=-7 | | 3y+14=13 | | 5x(x-6)= | | 3a(a+2)= | | 4+2*n=10 | | ln(8x-1)=5 | | d^2-8d+4=0 | | 18-4*2=l | | p(p-8)= | | 18-4*2=k | | 3x+6=-45 | | 5*c=78 | | 2w+2(4w)+w=329 | | x^2+11x-28=9x-4 | | 5n+3=2n-6 | | 32+z=126 | | 2z-3z-8z+y=z | | 2z-3z-8z+y=x | | (y-2)+(y-1)+y=-3 | | 80-6x=80 | | 6(4+2w)=-2(w-10) | | 5+5x-10+8x=11 | | 16x^3y^4+14x^2y^2z+3xz^2=0 |